Versatile role of Pseudomonas fuscovaginae cyclic lipopeptides in plant and microbial interactions - Ferrarini, Enrico; Špacapan, Mihael; Lam, Van Bach; McCann, Andrea; Cesa-Luna, Catherine; Marahatta, Bishnu Prasad; De Pauw, Edwin; De Mot, René; Venturi, Vittorio; Höfte, Monica (Frontiers in Plant Science, 2022)
Pseudomonas fuscovaginae is the most prominent bacterial sheath rot pathogen, causing sheath brown rot disease in rice. This disease occurs worldwide and it is characterized by typical necrotic lesions on the sheath, as well as a reduction in the number of emitted panicles and filled grains. P. fuscovaginae has been shown to produce syringotoxin and fuscopeptin cyclic lipopeptides (CLPs), which have been linked to pathogenicity. In this study, we investigated the role of P. fuscovaginae UPB0736 CLPs in plant pathogenicity, antifungal activity and swarming motility. To do so, we sequenced the strain to obtain a single-contig genome and we constructed deletion mutants in the biosynthetic gene clusters responsible for the synthesis of CLPs. We show that UPB0736 produces a third CLP of 13 amino acids, now named asplenin, and we link this CLP with the swarming activity of the strain. We could then show that syringotoxin is particularly active against Rhizoctonia solani in vitro. By testing the mutants in planta we investigated the role of both fuscopeptin and syringotoxin in causing sheath rot lesions. We proved that the presence of these two CLPs considerably affected the number of emitted panicles, although their number was still significantly affected in the mutants deficient in both fuscopeptin and syringotoxin. These results reveal the importance of CLPs in P. fuscovaginae pathogenicity, but also suggest that other pathogenicity factors may be involved.